Mapping of environmental supporting capacity based on ecosystem services in Wajo Regency 2021. Issue 1 (October 2021) - Makkasau, A R; Malamassam, D; Umar, A
Abstract: Population growth causes an increase in economic activity that occurs all the time. This has an impact on increasing the need for space for settlements and other needs to support human life. The carrying capacity of the environment is very important. A decrease in the carrying capacity for food production can lead to humanitarian and ecological disasters, such as food and water insecurity. Large-scale deforestation for agriculture in the tropics is an example of land cover change negative impact on the natural ability to support human needs. Uncontrolled land use dynamics will result in biophysical changes in the landscape that tend to be destructive. This dynamic also has an impact on exceeding the carrying capacity of the environment. Wajo Regency has the potential of natural resources, especially in the agricultural sector. Most of Wajo Regency is fertile and has potential for agricultural development. This is a special concern for local governments in improving the farmers' economy and supporting national food security. The rapid development also accelerates the conversion of land functions, and puts pressure on the sustainability of the food supply ecosystem. The results of the interpretation of Sentinel 2 Imagery (2020), Wajo Regency is dominated by rice fields (114, 296 Ha). The landscape map of Wajo Regency is dominated by undulating, wavy folds structural plains, made of non-carbonate sedimentary rock. From data analysis using the Analytical Hierarchy Process (AHP) method for food supply, water supply, protection against natural disasters, as well as flow management and flood protection, five classification classes were obtained: very high, high, medium, low and very low.